Short Communication: Diversity, biomass, and carbon stock of seagrass community in three coastal waters of Minahasa Peninsula, North Sulawesi, Indonesia - BILLY T. WAGEY; CAROLUS PARUNTU; RIDWAN LASABUDA; ALEX KAMBEY (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wagey BT, Paruntu C, Lasabuda R, Kambey A. 2023. Short Communication: Diversity, biomass, and carbon stock of seagrass community in three coastal waters of Minahasa Peninsula, North Sulawesi, Indonesia. Biodiversitas 24: 1793-1798. Seagrasses are well-known for their ecological and economic importance. However, just like any other ecosystem, seagrass meadows around the world are threatened by anthropogenic activities. This paper aimed to analyze the seagrass abundance (expressed as shoot density), richness, diversity, biomass, and carbon stocks in three locations in the Minahasa Peninsula of North Sulawesi, Indonesia. Transect survey techniques were conducted in Bajo, Bolsel and Bunaken. The study recorded 8 species across the three locations with Bolsel having the highest number of species (7), followed by Bajo (6) and Bunaken (4). Seagrass species differed significantly in terms of shoot density across the sampling locations in which denser shoots were observed for the eelgrass (Enhalus acoroides) at Bolsel while the other two species (Thalassia hemprichii and Cymodocea rotundata) were least abundant at the Bunaken site. Seagrass cover did not vary significantly between sites. With the exception of Bunaken, above-ground and below-ground biomasses, as well as carbon stock, did not differ among locations. The lower species diversity as well as above-ground biomass and carbon stocks in Bunaken were likely due to grazing by herbivores (e.g., fish and sea urchins) and tourism activities (e.g., boat traffic, diving, snorkeling). Grazing effects and human tourism activities should be included in future investigations to monitor the dynamics of seagrass biomass and carbon stocks in the area. This study provides baseline information that can be used to better manage the seagrass ecosystems, not only in the Minahasa Peninsula but in Indonesian waters and even beyond.